Improving water use for dry season agriculture by marginal and tenant farmers : A Compilation of Case Studies Vol. 1, 2 and 3 - CGIAR Research Program on Water, Land and Ecosystems (2019)
A series of outcome case studies are documented in three volumes covering individual stories and community outcomes. The innovataive combination of farmer group collectives with social and techical interventions led to the impacts. The primary beneficiaries are tenent and landless farmers participating in the project. The project interventions have resulted in a veriety of positive social and eocnomic impacts on partic;ipating marginal farmers indivually and in groups.